Effect of multidisciplinary cardiac rehabilitation on the response to cardiac resynchronization therapy. Issue 6 (12th October 2018) - Martens, Pieter; Jacobs, Guy; Dupont, Matthias; Mullens, Wilfried
Summary: Background: Both cardiac resynchronization therapy (CRT) and Multidisciplinary Cardiac Rehabilitation (CR) beneficially influence symptomatic status, exercise capacity, quality of life, and heart failure readmission rates. However, the interaction between both therapies remain incompletely addressed. Methods: Consecutive CRT patients implanted in a single tertiary care center were retrospectively analyzed. Patients were dived according to the participation in a structured CR‐program following CRT‐implant. The effect on functional status (New York Heart Association; NYHA‐class), reverse remodeling (change in left ventricular ejection fraction; LVEF), and the combined endpoint of heart failure readmission and all‐cause mortality was assessed after multivariate correction. Results: A total of 655 patients were analyzed of whom 223(34%) did and 432(66%) did not participate in a structured multidisciplinary CR‐program following implant. No adverse events relating to exercise training occurred during the CR‐program. Patients who participated in the CR‐program had a more pronounced improvement in NYHA‐class at 6‐months ( P = 0.006), even after multivariate correction (β = −0.144; 95% CI = [−0.270; −0.018]; P = 0.025). Maximal workload and VO2max on CPET at 6 months improved significantly even after adjustment ( P < 0.001, respectively P = 0.017). At 6‐months, CR associated with more improvement in LVEF (+11.9 ± 13 vs +14.5 ± 11; P = 0.008), however, this relationship was lost after multivariate correction ( P = 0.136). During 36 ± 22 months follow‐up, patients in the CR group had a higher event‐free survival for the combined endpoint ( P = 0.001), even after multivariate correction (adjusted HR = 0.547; CI = 0.366‐0.818; P = 0.003). Conclusions: Following CRT‐implant, the participation in a structured CR‐program is safe and beneficially influences symptomatic response and clinical outcome. The beneficial effects of exercise training are potentially independent and additive to the beneficial reverse remodeling effect induced by CRT itself.